Excited State Dynamics of a Self‐Doped Conjugated Polyelectrolyte. (23rd December 2019) - Tsokkou, Demetra; Peterhans, Lisa; Cao, David Xi; Mai, Cheng‐Kang; Bazan, Guillermo C.; Nguyen, Thuc‐Quyen; Banerji, Natalie
Abstract: The growing number of applications of doped organic semiconductors drives the development of highly conductive and stable materials. Lack of understanding about the formation and properties of mobile charges limits the ability to improve material design. Thus the largely unexplored photophysics of doped systems are addressed here to gain insights about the characteristics of doping‐induced polarons and their interactions with their surroundings. The study of the ultrafast optical processes in a self‐doped conjugated polyelectrolyte reveals that polarons not only affect their environment via Coulomb effects but also strongly couple electronically to nearby neutral sites. This is unambiguously demonstrated by the simultaneous depletion of both the neutral and polaronic transitions, as well as by correlated excited state dynamics, when either transition is targeted during ultrafast experiments. The results contrast with the conventional picture of localized intragap polaron states but agree with revised models for the optical transitions in doped organic materials, which predict a common ground level for polarons and neighboring neutral sites. Such delocalization of polarons into the frontier transport levels of their surroundings could enhance the electronic connectivity between doped and undoped sites, contributing to the formation of conductive charges. Abstract : The ultrafast photophysical properties of a self‐doped conjugated polyelectrolyte are experimentally studied to shed light on optoelectronic properties of doping‐induced polarons and their interactions with their surroundings. Here, important evidence that polarons not only affect their environment via Coulomb effects but also strongly couple electronically to nearby neutral sites is provided.